Deixis Analysis on Zootopia Movie Script: A Pragmatic Study - Budiarta, I Wayan; Gaho, Rahmat (IJOLTL (Indonesian Journal of Language Teaching and Linguistics), 2021)
This research is motivated by an interest in literacy particularly the script of films. This study aims to analyze the types of deixis on Zootopia movie scripts. This study is designed by using the quantitative and qualitative descriptive approaches. The data used in this study was the script of Zootopia film. Entirely, this research only focusing on analyzing the types of deixis in every scene of the movie. In this film, there are 41 scenes but only 15 scenes were selected for data analysis. The data was presented in tables and used diagrams in providing the tendency of deixis used on Zootopia movie script. The results showed that types of person deixis were 83%, discourse deixis 8%, time deixis 7%, spatial deixis 2% while other types 8%. In conclusion, there are all types of deixis were found in the Zootopia movie script, especially the type of time deixis found in various kinds of temporal category as many as 29 expressions such as next time, tomorrow, today, before noon, later, ago, soon, once a month, since, three hundred days, sixty-five days, five years, six years and a thousand years.